2020
DOI: 10.1101/2020.01.31.928200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LAG3 is a Central Regulator of NK Cell Cytokine Production

Abstract: 25Natural killer (NK) cells are innate effectors, which play a crucial role in controlling 26 viral infections. Administration of IFN-α has shown promising results as a therapeutic, 27 controlling HIV, and chronic viral hepatitis. However the downstream mechanisms by which 28 IFN-α mediates its anti-viral effects is largely unknown. In this investigation, we evaluated 29 the impact of IFN-α on peripheral blood NK cells from healthy donors. High dimensional 30 flow cytometry analysis of NK cell surface recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…The function of LAG-3 on NK cells was not well investigated and controversial. However, a factual finding was that inhibition of LAG-3 could increase the secretion of interferon-gamma (IFN-γ), tumor necrosis factoralpha (TNF-α), macrophage inflammatory proteins-1 alpha (MIP-1α), MIP-1β, and granulocyte-macrophage colony-stimulating factor (GM-CSF) (44). In this way, the expression of LAG-3 could collaborate with the inhibition of NK cell functions from KIR2D.…”
Section: Discussionmentioning
confidence: 99%
“…The function of LAG-3 on NK cells was not well investigated and controversial. However, a factual finding was that inhibition of LAG-3 could increase the secretion of interferon-gamma (IFN-γ), tumor necrosis factoralpha (TNF-α), macrophage inflammatory proteins-1 alpha (MIP-1α), MIP-1β, and granulocyte-macrophage colony-stimulating factor (GM-CSF) (44). In this way, the expression of LAG-3 could collaborate with the inhibition of NK cell functions from KIR2D.…”
Section: Discussionmentioning
confidence: 99%
“…However, how relevant they are for NK cells remains to be investigated and the significance of LAG-3 expression in NK cells remains largely unclear [ 70 ]. Recently, it was shown that LAG-3 is preferentially expressed on CD56 dim NK cells after IFN-α treatment and acts specifically as a negative regulator of cytokine production without compromising cytotoxic function [ 93 ]. Another candidate, TNF receptor family member, OX40 is expressed on leukemic blasts in a substantial percentage of patients with AML and promotes activation and proliferation of T cells.…”
Section: Modifying Nk Cells To Be Better Effector Cellsmentioning
confidence: 99%
“…A more recent analysis of the status of LAG-3 on the NK cell surface following exposure to IFN-α demonstrated an increased expression of LAG3 ( 239 ). This paper proposes more studies on the impact of other cytokines on these IRs, and questions whether a single cytokine or a group of them cooperate and upregulate the IR, and/or one cytokine triggers one or array of other chemokines.…”
Section: Nk Cell Irsmentioning
confidence: 99%
“…Further characterization showed that LAG3 was expressed in the NK cells populations that show high expression of activation and maturation markers. Additionally, in-vitro LAG3 blocking on NK cells using mAb led to an increase in the production of cytokines IFN-γ, TNF-α, MIP-1α and MIP-1β, without affecting the cytotoxic activity, which suggests that LAG3 is a negative regulator of cytokine production by mature NK cells ( 239 ).…”
Section: Nk Cell Irsmentioning
confidence: 99%
See 1 more Smart Citation